2021
DOI: 10.1038/s41386-021-01129-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumbofrontal tract integrity is related to early life adversity and feedback learning

Abstract: Abuse, neglect, exposure to violence, and other forms of early life adversity (ELA) are incredibly common and significantly impact physical and mental development. While important progress has been made in understanding the impacts of ELA on behavior and the brain, the preponderance of past work has primarily centered on threat processing and vigilance while ignoring other potentially critical neurobehavioral processes, such as reward-responsiveness and learning. To advance our understanding of potential mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…For example, in a large cohort of adults ( N = 3036 ), higher childhood adversity exposure was associated with smaller caudate volumes ( 71 ). Childhood trauma is also related to lower white matter integrity in fiber tracts connecting the caudate, ventral striatum, and prefrontal cortex ( 46 , 72 , 73 ). However, rodent models of ELS (discussed below) suggest changes in reward circuitry are at the level of excitatory and neuromodulatory signaling rather than gross structural changes.…”
Section: Impact Of Early Life Stress On Human Reward Processing and Connectivitymentioning
confidence: 99%
“…For example, in a large cohort of adults ( N = 3036 ), higher childhood adversity exposure was associated with smaller caudate volumes ( 71 ). Childhood trauma is also related to lower white matter integrity in fiber tracts connecting the caudate, ventral striatum, and prefrontal cortex ( 46 , 72 , 73 ). However, rodent models of ELS (discussed below) suggest changes in reward circuitry are at the level of excitatory and neuromodulatory signaling rather than gross structural changes.…”
Section: Impact Of Early Life Stress On Human Reward Processing and Connectivitymentioning
confidence: 99%
“…At a broad level, we noted only modest associations between stress exposure and the three brain morphometrics measured in our study. This stands in stark contrast with the widespread reductions in frontoparietal regions reported elsewhere (Baker et al., 2012 ; Cohen et al., 2006 ; Gold et al., 2016 ; Hodel et al., 2015 ; Kelly et al., 2013 ; Kennedy et al., 2021 ; Mackes et al., 2020 ; McLaughlin et al., 2014 ; Teicher, 2006 ; Thomaes et al., 2010 ). There are multiple explanations for these potential discrepancies.…”
Section: Discussionmentioning
confidence: 58%
“…That is, early maltreatment experiences disrupted neural development, particularly in the frontoparietal system (i.e., cognitive ToM) governing response inhibition and cognitive control (Chen et al, 2013), which in turn, might result in greater attentional impulsive tendencies later in life. In fact, previous studies have documented similar findings that the white matter tract (e.g., cingulum and accumbofrontal) integrity mediated the association between child abuse and trait anxiety (Tendolkar, Martensson, Kuhn, Klumpers, & Fernandez, 2018) and negative feedback sensitivity (Kennedy et al, 2021). It suggested that CM triggered neurocognitive alterations, especially, parietal–frontal circuits alteration that heightens impulsivity and increases vulnerability to risky behavior.…”
Section: Discussionmentioning
confidence: 58%